العلاقة الوثيقة الثقافية بين الهند وإندونيسيا - muhammad azhar (UIN Fatmawati Sukarno Bengkulu, 2019)
AbstractIndia and Indonesia have historical relations for ages. Indian cultures are flourished and preserved by the Indonesian people. Although Indonesia is a Muslim country, in terms of Culture, Indonesia is influenced by Indian traditions and customs. India and Indonesia have shared two millennia of close cultural and commercial contacts. The Hindu, Buddhist and later Muslim faith traveled to Indonesia from the shores of India. Indonesian folk art and dramas are based on stories from the great epics of Ramayana and Mahabharata. The shared culture, colonial history and post-independence goals of political sovereignty, economic self-sufficiency, and independent foreign policy have a unifying effect on the bilateral relations.In this article, The researcher will try to explain the meanings of culture and will discuss the importance of the same. The paper will also shed lights on the historical relations between India and Indonesia from Ramayana till the date.